TREatment of ATopic eczema (TREAT) Registry Taskforce: an international Delphi exercise to identify a core set of domains and domain items for national atopic eczema photo‐ and systemic therapy registries. (1st April 2019) - Gerbens, L.A.A.; Apfelbacher, C.J.; Irvine, A.D.; Barbarot, S.; de Booij, R.J.; Boyce, A.E.; Deleuran, M.; Eichenfield, L.F.; Hof, M.H.; Middelkamp‐Hup, M.A.; Roberts, A.; Schmitt, J.; et al.
Summary: Background: Evidence of immunomodulatory therapies to guide clinical management of atopic eczema (AE) is scarce, despite frequent and often off‐label use. Patient registries provide valuable evidence for the effects of treatments under real‐world conditions that can inform treatment guidelines, give the opportunity for health economic evaluation and the evaluation of quality of care, as well as pharmacogenetic and dynamic research, which cannot be adequately addressed in clinical trials. Objectives: The TREatment of ATopic eczema (TREAT) Registry Taskforce aims to seek international consensus on a core set of domains and items ('what to measure') for AE research registries, using a Delphi approach. Methods: Participants from six stakeholder groups were included: doctors, nurses, nonclinical researchers, patients, industry and regulatory body representatives. The eDelphi comprised three sequential online rounds, requesting participants to rate the importance of each proposed domain item. Participants could add domain items to the proposed list in round 1. A final consensus meeting was held to ratify the core set. Results: Participants ( n = 479) from 36 countries accessed the eDelphi platform, of whom 86%, 79% and 74% completed rounds 1, 2 and 3, respectively. At the face‐to‐face consensus meeting attended by 42 participants the final core set was established containing 19 domains with 69 domain items (49 baseline and 20 follow‐up items). Conclusions: This core set of domains and items to be captured by national AE systemic therapy registries will standardize data collection and thereby allow direct comparability across registries and facilitate data pooling between countries. Ultimately, it will provide greater insight into the effectiveness, safety and cost‐effectiveness of photo‐ and systemic immunomodulatory therapies.